Pengaruh Imbangan Tepung Ubi Jalar Ungu (Ipomoea batatas L.) dan Tepung Mocaf (Modified Cassava Flour) pada Karakteristik Pie - Auliyah, Fitri; Putranto, Kelik (Jurnal Dimamu, 2025)
This research aimed to determine the optimal ratio of purple sweet potato flour and mocaf flour to achieve the best characteristics of milk pie, focusing on water content, organoleptic properties, carbohydrate content, and crude fiber. The research was carried out at the Chemistry and Food Processing Laboratories of the Faculty of Agriculture, Ma'soem University, with chemical testing conducted at the Chemistry Laboratory of Bakti Asih Bandung College and the Food Technology Laboratory at the Faculty of Engineering, Pasundan University, from March to July 2024. The experimental method used was a Randomized Group Design (RAK). The treatments included varying proportions of purple sweet potato flour and mocaf flour at 70%:30%, 60%:40%, 50%:50%, 40%:60%, and 30%:70%, with each treatment repeated five times. The analysis covered water content, carbohydrate content, crude fiber content, and organoleptic evaluation, including color, aroma, taste, and texture of the milk pie. The findings revealed that a 60% purple sweet potato flour and 40% mocaf flour ratio produced the best milk pie characteristics, based on preference levels for color (3.76 - liked), aroma (4.04 - liked), and texture (3.68 - liked), along with a carbohydrate content of 12.19% and crude fiber of 3.98%.